THE EVOLUTION AND IMPACT OF CURRENCY IN THE SHAYBANID KHANATE’S ECONOMIC STRUCTURE (TAMADDUN NURI JURNALI, 2024)
Research Objectives: This study aims to analyze the role of the tenge currency in the economic structure of the Shaybani Khanate from the 16th century, focusing on its minting, value fluctuations, and its broader implications on trade and governance.